Computing norm's benefit awareness via norm adoption ratio and norm morality - Itaiwi A.-M.K.; Ahmad M.S.; Tang A.Y.C.; Mahmoud M.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Agents; Robotics; Detection algorithm; Norm's Adoption; Norm's Awareness; Norm's Morality; Novel concept; Strength formulas; Multi agent systems